Tinjauan Hukum Islam terhadap Konsep Subrogasi dalam Asuransi Syari’ah - Anwar Ma'rufi (Indonesia, 2019)
Islamic insurance products and services adopt many conventional insurance mechanisms including subrogasi. In the aplication, it turned out to contain many problems. Therefore, author was intersted in studying criticaly. This papper was discussed by library research. The approach that used was normatif. The theories that used were the hawālah and takāful/tadāmun concepts. This papper had found that subrogasi was not suitable with islamic law (according to scholar of Hanafi, Maliki, Syafi’i, and Hanabilah) if it was aplicated in islamic insurance because the claim fund was taken from tabarru’ fund acumulation, not from insurance fund. Because of subrogasi contains the advantage and harmfull in islamic insurance, author recomend in order to use wakalah theory. The manager of islamic insurance is positioned as a representative of member to demand compensation against the gulty person